Verification of dose estimation of Auger electrons emitted from Cu-64 using a combination of FNTD measurements and Monte Carlo simulations. (March 2020) - Kusumoto, Tamon; Matsuya, Yusuke; Baba, Kentaro; Ogawara, Ryo; Akselrod, Mark S.; Harrison, Jonathan; Fomenko, Vasiliy; Kai, Takeshi; Ishikawa, Masayori; Hasegawa, Sumitaka; Kodaira, Satoshi
Abstract: We report the dose measurement technique for emitted particles from Cu-64 source using a combination of Fluorescent Nuclear Track Detector (FNTD), which is Al2 O3 single crystal doped with C and Mg, and Monte Carlo simulations in the PHITS code and Geant4 toolkit. The relatively high fluorescence intensity induced by Auger electrons is observed at the FNTD surface. Then, the fluorescence intensity monotonically reduces as the depth from the surface increases. The results obtained using the PHITS Monte Carlo simulation code is very similar to that of Geant4. Also, the simulations are in good agreement with experimental results. These findings prove that the signal induced by Auger electrons is successfully measured using FNTD. Additionally, the high signal at the FNTD surface implies that Auger electrons can work effectively to kill cancer cells proximal to a Cu-64 source while minimizing damage effects on normal cells distal to the source. At 15 μm depth in the crystal, which is the mean tissue cell radius, the relative dose of beta particles is about 24% of that at the FNTD surface. Therefore, the contribution of free radicals created by beta particles should be accounted for to clarify the impact of Cu-64 on tissues. Highlights: Absorbed dose of Auger electrons is accurately measured using FNTD. The experimental results are well agreement with the simulations. When the contribution of Auger electrons is not considered, simulations don't agree with experiments.